Pemanfaatan Eco Enzyme Sebagai Pupuk Cair Di KWT Sekar Melati - Titiaryanti, Ni Made; Hastuti, Pauliz Budi; Mardhatilah, Dina (LPPM IST AKPRIND Yogyakarta, 2022)
The yard of the house can provide benefits for family life if it is managed properly, can be planted with various vegetables and family medicinal plants (aloe vera) and can be an important part in supporting food security. Household waste in the form of vegetable residues, fruit peels that have been considered waste can be converted into multipurpose eco-enzyme fluids. The purpose of the community service activity is to train and set an example for the Women Farmers Group (WFG)Sekar Melati in Sanggrahan, Plumbon, Banguntapan, Bantul, Yogyakarta, to make eco-enzymes from vegetable waste and fruit peels including aloe vera skin as liquid organic fertilizer for vegetable crops and as a disinfectant. Problems faced include WFG not knowing how to manufacture and benefiting from eco-enzyme (EE) from fruit peel waste and vegetable residue. The yard land has not been optimally utilized, does not know the correct plant cultivation techniques in polybags, especially the manufacture of planting media and plant maintenance. To find solutions to these problems, counseling and training on EE manufacturing technology were carried out. Transfer of technology for the cultivation of organic vegetables and family medicinal plants (aloe vera). The results of the WFG activities that have been carried out are that the partner group Sekar Melati is very enthusiastic in participating in all the community service activities provided. WFG Sekar Melati has been able to make eco enzyme, apply eco enzyme as liquid organic fertilizer and disinfectant. WFG Sekar Melati already knows how to make the right planting media for planting vegetable seeds and aloe vera for use in the yard.